2023
DOI: 10.1111/iwj.14198
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of ferroptosis‐related genes in diabetic foot using bioinformatics analysis

Abstract: Ferroptosis is a novel form of cell death that plays a key role in several diseases, including inflammation and tumours; however, the role of ferroptosis‐related genes in diabetic foot remains unclear. Herein, diabetic foot‐related genes were downloaded from the Gene Expression Omnibus and the ferroptosis database (FerrDb). The least absolute shrinkage and selection operator regression algorithm was used to construct a related risk model, and differentially expressed genes were analysed through immune infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Finally, they screened out the iron deathrelated gene TP53, which may play a key role in the pathogenesis of diabetic foot ulcers and can serve as a potential biomarker. 76 In addition, studies have shown that MAFG and MAPK3 act as death-related genes that are relevant to DFUs and may become potential therapeutic targets for DFU patients. The higher accuracy of MAPK3 suggests that it may be a promising iron death-related biomarker.…”
Section: Ferroptosis In Dfusmentioning
confidence: 99%
“…Finally, they screened out the iron deathrelated gene TP53, which may play a key role in the pathogenesis of diabetic foot ulcers and can serve as a potential biomarker. 76 In addition, studies have shown that MAFG and MAPK3 act as death-related genes that are relevant to DFUs and may become potential therapeutic targets for DFU patients. The higher accuracy of MAPK3 suggests that it may be a promising iron death-related biomarker.…”
Section: Ferroptosis In Dfusmentioning
confidence: 99%